Analysis Of Implementation Of Puskesmas Accreditation Policy In Medan City In 2023 - Leo Erikson Sitepu; Donal Nababan; Frida Lina Tarigan (SEAN Institute, 2023)
Community health centers must be accredited to ensure good quality of service. Community health center accreditation is recognition given to community health centers after meeting accreditation standards. Medan City has 41 community health centers, 39 of which have been accredited, predominantly basic and intermediate status (87%). The preliminary study describes the problems in implementing community health center accreditation, including communication, resources, attitudes of leaders and employees, organizational structure and support from health services. The aim of the research is to analyze the implementation of community health center accreditation policies in Medan City. This research uses a descriptive analysis method with a qualitative approach by means of observation, in-depth interviews and collecting documentation from research informants. The selection of research informants used purposive sampling. The main informants are people who are directly involved in implementing accreditation policies at community health centers. Research variables include communication, resources, disposition/attitude, organizational structure, and health service support. The research results show that communication at the community health center is running well, but the instruments and standards for community health center accreditation are still poorly understood. Human resources are not distributed evenly and some have excessive workloads, budget support and facilities are not optimal. The attitude of officers in general is good towards accreditation, but the distribution of tasks is not fair and equitable. The organizational structure has been determined, work procedures are in place. However, the commitment of the leadership and officers to carry out accreditation has not been developed. The health department supports the implementation of accreditation. However, coaching and supervision has not been scheduled and is not continuous. The conclusion was that communication, resources, disposition/attitude, organizational structure, and support from the health service were not fully functioning well, and obstacles were found in understanding and fulfilling accreditation standard documents. Suggestions for more intense, sustainable and quality guidance for community health centers in implementing accreditation policies.